Towards a better understanding of Xenophyllum esquilachense (Senecioneae, Compositae), a poorly known Andean species - Calvo, Joel; Muñoz-Schick, Mélica; Moreira-Muñoz, Andrés (Phytotaxa, 2018)
Xenophyllum esquilachense is a poorly known Andean species that was hitherto considered endemic to southern Peru. It is recorded for the first time from Bolivia and northern Chile, and the name Senecio pfisteri is synonymized with it. New insights on its global occurrence, ecology, and taxonomy are provided, as well as pictures of living plants and an updated dichotomous key to the Xenophyllum species from southern Andes.